If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(p + 5q + -13) = 0 Reorder the terms: 5(-13 + p + 5q) = 0 (-13 * 5 + p * 5 + 5q * 5) = 0 (-65 + 5p + 25q) = 0 Solving -65 + 5p + 25q = 0 Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '65' to each side of the equation. -65 + 5p + 65 + 25q = 0 + 65 Reorder the terms: -65 + 65 + 5p + 25q = 0 + 65 Combine like terms: -65 + 65 = 0 0 + 5p + 25q = 0 + 65 5p + 25q = 0 + 65 Combine like terms: 0 + 65 = 65 5p + 25q = 65 Add '-25q' to each side of the equation. 5p + 25q + -25q = 65 + -25q Combine like terms: 25q + -25q = 0 5p + 0 = 65 + -25q 5p = 65 + -25q Divide each side by '5'. p = 13 + -5q Simplifying p = 13 + -5q
| 6(5x-2)(2x+3)=0 | | 9(X-3)/3=6(X+2)/12 | | -4y^2=24y | | -7(x-7)-6=43 | | x^2/3-x/2-35/6=0 | | 3y+x=4x+-3 | | 16/-11=n/29 | | -5(3T-5)+2T=6T-5 | | 37/y=7/3 | | -2cos^2x+5=5sinx | | p^2xP^6= | | 3(2X+3)=6X+9 | | (3x+8/5)-7=-x+9 | | 3(p+6q-14)= | | 3x+8/5-7=-x+9 | | 7x+9=7(x+8) | | 4/0.8=0.3/w | | 0.50X+0.35(70)=36.5 | | 0.9/0.5=z/4.5 | | 2x^2-0=14 | | 45/50=m/100 | | x/7=8/21 | | (x-5)(x^2+2x+5)= | | 6y+2-8y=3-2y-10 | | =-2(7+6n) | | -4(x-1)-(2-x)=-6 | | -5/9y-(y-5/6)=1/54(y-6) | | 16x+8y=-17 | | 8n+10-2n=3n-2+5n | | 8n+10-22=3n-2+5n | | -2x-10=4+5x | | -3-2x=18 |